TOXICITY STUDY OF PARE LEAF EXTRACTS (MOMORDICA CHARANTIA) TO CULEX PIPIENS MOSQUITO LARVAE - Annisa, Rahmi; Amir, Muhammad; Kuncoro, Hadi (Journal of Islamic Pharmacy, 2017)
This study aims to determine the yield, toxicity, and toxic concentration of crude extracts of ethanol, n-hexane fraction extract, ethyl acetate fraction extract and n-butanol fractions extract pare leaf (Momordica charantiaL.) larvae Culex pipiens. The method used to determine the toxicity of extract larvasida test larvae Culex pipiens to obtain the LC99 values obtained using the analysis of Reed and Muench. Extraction and fractionation processis known to yield a ethanol crude extract obtained 8.86%, n-hexane fraction extract of 1%, ethyl acetate fraction extract 1.80% and n-butanol fractions extract of 0.80% and the toxicity obtained test results that pare leaf (Momordica charantia L.) have the potential toxicity larvae larvae of Culex pipiens as indicated by the value by Lethality Concrentation 99 % (LC99) in the crude extract ethanol 7416.52Â  ppm, n-hexane fraction extract of 2564.48 ppm, ethyl acetate fraction extract 2702.09 ppm and n-butanol fractions extract of 2665.63 ppm.Â Keywords: Pare leaf (Momordica charantia L.), toxicity, larvae Culex pipiens